2006
DOI: 10.1634/stemcells.2006-0167
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Is Expressed by Putative Stem/Progenitor Cells and Melanocytes in the Human Limbal Epithelial Stem Cell Niche

Abstract: Corneal epithelial stem cells are known to be localized to the basal layer of the limbal epithelium, providing a model system for epithelial stem cell biology; however, the mechanisms regarding the maintenance of these stem cells in their specialized niche remain poorly understood. Ncadherin is a member of the classic cadherin family and has previously been demonstrated to be expressed by hematopoietic stem cells. In the present study, we demonstrate that N-cadherin is expressed by putative stem/ progenitor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 42 publications
8
102
1
1
Order By: Relevance
“…However, in this study, Ncadherin expression has been shown to be lost during the in vitro culture of those cells. These data suggest that Ncadherin is an important cell-to-cell adhesion mediator between LESC and their niche and potentially marks these cells in vivo; however, it is not useful as an in vitro putative stem cell marker (Hayashi et al 2007). …”
Section: Other Important Markersmentioning
confidence: 99%
“…However, in this study, Ncadherin expression has been shown to be lost during the in vitro culture of those cells. These data suggest that Ncadherin is an important cell-to-cell adhesion mediator between LESC and their niche and potentially marks these cells in vivo; however, it is not useful as an in vitro putative stem cell marker (Hayashi et al 2007). …”
Section: Other Important Markersmentioning
confidence: 99%
“…Unlike that of the cornea, the basement membrane of the limbus is undulating with papillae or 'pegs' of stroma extending upward [54] and fenestrated [55,56]; these anatomic features in the limbus suggest that limbal epithelial SCs might closely interact with cells in the underlying limbal stroma (Figure 2). The preferential expression of a9 integrin [19] and N-cadherin [26] without connexin 43 [11] also suggests that limbal SCs interact with unique extracellular components in the niche. Compositionally, other than laminin-1 and laminin-5, the limbal basement membrane also expresses laminin a2b2 chains, while the corneal basement membrane does not.…”
Section: Where Is the Limbal Stem Cell Niche?mentioning
confidence: 99%
“…In contrast, the SC-containing limbal epithelium has a high proliferative potential in different cultures [12][13][14][15], and their in vitro proliferation is resistant to the inhibition by tumor-promoting phorbol esters [13,16,17]. Furthermore, limbal basal epithelial cells express cytokeratin 19 [18], and integrin a9 [10,19], and preferentially express such progenitor markers as p63 [20], especially its ∆Np63a isoform [21,22], Bcrp1/ABCG2 [10,[23][24][25], and N-cadherin [26].…”
Section: Introductionmentioning
confidence: 99%
“…In the basal layers of the interpalisade rete ridges, small, round cells, exhibiting morphological features of primitive stem cells were shown (16,38,100,101). Protection of stem cells is thought to be fulfilled by three attributes of the palisades: they are situated in those parts of the cornea that are most protected by the eyelids; they contain melanocytes that safeguard stem cells from UV radiation by the transfer of melanin granules (35,38,102,103); in addition, protection from mechanical shear forces is provided at the bottom of the rete pegs. The palisade ridge regions contain blood vessels that can provide nutrients and other supportive factors for the SCs (1,39,58,101).…”
Section: The Limbal Epithelial Stem Cell Nichementioning
confidence: 99%